ENABLING FACTORS FOR THE EXISTENCE OF WASTE PICKERS: A SYSTEMATIC REVIEW - Schenck, Rinie; Blaauw, Derek; Viljoen, Kotie (Social Work/Maatskaplike Werk, 2016)
The paper reports on a systematic review research process to determine the enabling factors for waste pickers to operate in the informal economy in South Africa. Twenty-eight South African journal articles, theses and position and policy papers were sourced and appraised. The results indicate that recognition of the waste pickers in the waste system is the most enabling factor for them to operate. The concept of recognition is analysed, described and explained as assisting waste pickers to become more visible, having a voice and to be validated.